Redescription of Ichthyouris bursata Moravec & Prouza, 1995 (Nematoda: Pharyngodonidae), a parasite of wild and aquarium-reared discus Symphysodon spp. (Osteichthyes) - Moravec, Frantisek; Laoprasert, Thitiporn (Systematic parasitology, 2008)
The oxyuroid nematode Ichthyouris bursata Moravec & Prouza, 1995 (Pharyngodonidae) was recorded from the intestine of discus (Symphysodon spp. and hybrids) cultured in discus farms in Bangkok and Nonthaburi, central Thailand, during 2006 and 2007. This material made it possible to study in detail the morphology of this little known parasite species, using both light and scanning electron microscopy (the latter not previously used for the male). The SEM examination showed taxonomically important morphological features not previously reported or erroneously described, including the presence of three bilobed lips, a pair of sclerotised plate-like structures and a median cone-shaped outgrowth on the posterior cloacal lip, short 'hairs' on the cloacal lips, digital phasmids in the male and, sometimes, up to two filaments on the egg poles. This species is of South American origin, which was confirmed by its recent record from a free-living blue discus S. aequifasciatus Pellegrin in Brazil. The reproduction and transmission of I. bursata in the conditions of aquarium tanks is probably permitted by the direct (homoxenous) life-cycle of this parasite.
Keywords: Oxyurida Infections; Animals, Wild; Female; nemoci ryb; infekce hlísticemi řádu Oxyurida; Oxyurida; divoká zvířata; Animals; ženské pohlaví; Cichlids; mužské pohlaví; Male; zvířata; Fish Diseases; cichlidy